The relationship between oral health and quality of life of institutionalized Brazilian elderly: An integrative review (Research, Society and Development, 2023)
The increase in Brazilian life expectancy implies concern with ensuring the quality of life of the elderly, which encompasses several factors, including oral health. Aging with pathologies (senility) causes greater wear and tear on the oral cavity, which can exacerbate problems that affect chewing, function, and aesthetics in the elderly. Thus, the investigation of processes and policies, as well as complaints, regarding oral health care for the elderly is essential to publicize and help expand these services to most of the elderly population. This study is an integrative literature review carried out with the aim of identifying publications about the relationship between oral health and quality of life of the institutionalized elderly. The analyzed studies report the negative self-perception of the elderly in relation to their oral health, highlighting as limiting factors the difficulty of accessing services and the lack of guidance for elderly and their caregivers. The analysis of studies suggests that the development of public policies and the integrate work of health professionals, caregivers, and the elderly themselves within their conditions, may be the main way to take care of oral health in elderly, with special attention to institutionalized elderly population.